Bom Bunuh Diri dalam novel Junūdullah, karya Fawwaz Haddad: Studi analisis Altruism Suicide Emile Durkehim. - Rasyad, Munawir (`A Jamiy : Jurnal Bahasa dan Sastra Arab, 2023)
This study uses Emile Durkheim's theory of concepts altruism suicide as a basis for understanding the motive behind the act of suicide bombing in the novel "Junu>dullah" by Fawwaz Haddad. The research method used is descriptive qualitative method. This theory states that suicide bombings carried out by a person can sometimes be seen as an altruistic act, that is, an action taken for the benefit of a group or society, not for the sake of the individual alone. Through analysis of the novel "Junu>dullah”, the author finds that suicide bombings committed by jihadists are closely related to war situations with unequal forces militarily. So that the phenomenon of suicide bombings contained in the novel is more closely related to war tactics than as an expression of excessive religiosity. In addition, the suicide bombings are also driven by a very high sense of unity in society as reflected in the novel.